2018
DOI: 10.4049/jimmunol.1602017
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Alternative Pathway of Complement by Murine Factor H–Related Proteins

Abstract: Factor H (FH) is a key alternative pathway regulator that controls complement activation both in the fluid phase and on specific cell surfaces, thus allowing the innate immune response to discriminate between self and foreign pathogens. However, the interrelationships between FH and a group of closely related molecules, designated the FH-related (FHR) proteins, are currently not well understood. Whereas some studies have suggested that human FHR proteins possess complement regulatory abilities, recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…The authors concluded that mouse FHR-B similar to human FHR-1 and FHR-5 promoted complement activation via interaction with C3b and via competition with mouse FH ( 283 ). Similarly, it has been shown that mouse FHR-A and mouse FHR-B proteins antagonize the protective function of FH using sheep erythrocyte hemolytic assays and in two cell lines, kidney proximal tubular cell line and a human retinal pigment epithelial cell line (ARPE-19) ( 284 ). Lack of mouse FHR-C has been linked to an autoimmune disease ( 278 ).…”
Section: Mouse Models Of Human Rheumatoid Arthritismentioning
confidence: 96%
“…The authors concluded that mouse FHR-B similar to human FHR-1 and FHR-5 promoted complement activation via interaction with C3b and via competition with mouse FH ( 283 ). Similarly, it has been shown that mouse FHR-A and mouse FHR-B proteins antagonize the protective function of FH using sheep erythrocyte hemolytic assays and in two cell lines, kidney proximal tubular cell line and a human retinal pigment epithelial cell line (ARPE-19) ( 284 ). Lack of mouse FHR-C has been linked to an autoimmune disease ( 278 ).…”
Section: Mouse Models Of Human Rheumatoid Arthritismentioning
confidence: 96%
“…There was also no change in glomerular FHR staining. Little is known about the functions of the mouse FHR proteins, but they are able to interact with both C3b 27 , 28 and C3d. 27 In fact, the apparent affinity of both FHR-A and FHR-B for C3d is stronger than that of FH.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some FHRs were reported to promote alternative pathway activation by binding C3b and serving as a platform for the assembly of the C3 convertase ( 27 , 32 , 33 ). Recent characterization of some of the mouse FHRs supports a role of these proteins as positive regulators in the modulation of complement activation ( 34 , 35 ).…”
Section: Introductionmentioning
confidence: 97%